Integrating coaches into the national training programme: A modern approach to surgical supervision. (February 2018) - Ahmed, Faheem; Sheriff, Ibrahim H.N.; Al-Alusi, Mostafa; Ahmed, Na'eem; Lasoye, Tunji
Highlights: Surgical trainees are at high risk of burnout. Better supervision might help to diminish this risk and inspire trainees. Coaches could be appointed to support surgeons in training. A formal programme with incentives could attract a diverse number of coaches. Trainees can be matched to coaches from their area of interest for career direction.